Demonic grounds : black women and the cartographies of struggle - McKittrick, Katherine (University of Minnesota Press, 2006)
"Demonic Grounds moves between past and present, archives and fiction, theory and everyday, to focus on places negotiated by black women during and after the transatlantic slave trade. Specifically, Katherine McKittrick addresses the geographic implications of slave auction blocks, Harriet Jacobs's attic, black Canada and New France, as well as the conceptual spaces of feminism and Sylvia Wynter's philosophies." --Publisher's description.